Large-Scale Knowledge Resources. Construction and Application Construction and Application - Third International Conference on Large-Scale Knowledge Resources, LKR 2008, Tokyo, Japan, March 3-5, 2008, Proceedings - Tokunaga, Takenobu; Ortega, Antonio (Lecture Notes in Artificial Intelligence,, 2008)
Atthestartofthe21stcentury,wearenowwellonthewaytowardsaknowled- intensive society, in which knowledge plays ever more important roles. Thus, research interest should inevitably shift from information to knowledge, with the problems of building, organizing, maintaining and utilizing knowledge - coming centralissues in a wide varietyof ?elds. The 21stCentury COE program "Framework for Systematization and Application of Large-scale Knowledge - sources (COE-LKR)" conducted by the Tokyo Institute of Technology is one of several early attempts worldwide to address these important issues. Inspired by this project, LKR2008 aimed at bringing together diverse contributions in cognitive science, computer science, education and linguistics to explore design, construction, extension, maintenance, validation and application of knowledge. Respondingtoourcallforpapers,wereceived38submissionfromavarietyof researchareas.EachpaperwasreviewedbythreeProgramCommitteemembers. Since we were aiming at an interdisciplinary conference covering a wide range of topics concerning large-scale knowledge resources (LKR), each paper was assigned a reviewer from a topic area outside the main thrust of the paper. This reviewer was asked to assess whether the authors described the moti- tion and importance of their work in a comprehensible manner even for readers in other research areas. Following a rigorous reviewing process, we accepted 14 regular papers and 12 poster papers.